2021
DOI: 10.1021/acsomega.0c04649
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Buertai Coal Macromolecular Model and GCMC Simulation of Methane Adsorption in Micropores

Abstract: With the increase in high gas mines in the low coal rank mining area in the northwestern part of China, high gas mines in the low-rank coal mining area have caused many gas emission accidents. Coal is a porous material, containing a large number of micropores (<2 nm), which can absorb large amounts of methane, so it is necessary to explore methane adsorption in micropores of low-rank coal. In this work, FTIR, HRTEM, and 13 C-NMR were used to test the macromolecular structural parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The chemical structure analysis of the material was performed using a Thermo Fisher IN10 Fourier transform infrared spectrometer (Thermo Fisher Scientific, USA). The KBr pellet method was used with a resolution of 4 cm –1 and a scanning range of 4000–400 cm –1 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical structure analysis of the material was performed using a Thermo Fisher IN10 Fourier transform infrared spectrometer (Thermo Fisher Scientific, USA). The KBr pellet method was used with a resolution of 4 cm –1 and a scanning range of 4000–400 cm –1 …”
Section: Methodsmentioning
confidence: 99%
“…The KBr pellet method was used with a resolution of 4 cm −1 and a scanning range of 4000−400 cm −1 . 50 4.2.4. Low-Temperature Nitrogen Gas Adsorption− Desorption Test.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…Coal has the capability to adsorb methane easily, and it takes around 40 minutes to reach an equilibrium state. However, research into CH 4 adsorption simulation has shown that several micropores are closed and unable to adsorb CH 4 [23].…”
Section: Ch 4 Adsorption On Coalmentioning
confidence: 99%
“…The experimental NMR data were used as convergence criteria to adjust and refine the structural models, ensuring that the simulated 13 C NMR spectra of the models matched the experimental spectra. 38 The two-dimensional structural models constructed were subjected to molecular mechanics simulations using Material Studio software, including geometry optimization and molecular dynamics simulations. 39 Three-dimensional models with the lowest energy and stable structures were obtained.…”
Section: Ftirmentioning
confidence: 99%